Quadriceps and hamstrings coactivation in exercises used in prevention and rehabilitation of hamstring strain injury in young soccer players - Torres, G.; Chorro, D.; Navandar, A.; Rueda, J.; Fernández, L.; Navarro, E. (bioRxiv, 2019)
This study aimed to study the co-activation of hamstring-quadriceps muscles during submaximal strength exercises without the use of maximum voluntary isometric contraction testing and compare (i) the inter-limb differences in muscle activation, (ii) the intra-muscular group activation pattern, and (iii) the activation during different phases of the exercise. Muscle activation was recorded by surface electromyography of 19 elite male youth players. Participants performed five repetitions of the Bulgarian squat, lunge and the squat with an external load of 10 kg. Electrical activity was recorded for the rectus femoris, vastus medialis, vastus lateralis, biceps femoris and semitendinosus. No significant inter-limb differences were found (F1, 13=619; p=0.82; partial ?2=0.045). Significant differences were found in the muscle activation between different muscles within the muscle group (quadriceps and hamstrings) for each of the exercises: Bulgarian squat (F1,18=331: p<0.001; partial 2=0.80), lunge (F4,72=114.5; p<0.001; partial 2=0.86) and squat (F1,16=247.31; p<0.001; partial 2=0.93).Differences were found between the concentric, isometric and eccentric phases of each of the exercises (F2, 26=52.27; p=0.02; partial 2=0.80). The existence of an activation pattern of each of the muscles in the three proposed exercises could be used for muscle assessment and as a tool for injury recovery